The Determinant of Indonesian Cocoa Export Growth to the Main Export Destination Countries - Dwi Putri Jeng Ivo Nurun Nisa; Ernoiz Antriyandarti (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2023)
Indonesia remains the sixth largest cocoa producer globally, with exports predominantly comprising cocoa beans (60%).  As global cocoa demand and consumption increase, it is imperative that leading cocoa-producing countries, including Indonesia, capitalize on this trend. To facilitate informed future decisions, Indonesia must identify the key drivers of growth for its cocoa bean exports. This study analyses the factors influencing the growth of Indonesia's cocoa bean exports to five key export destinations, namely Malaysia, America, India, China, and the Netherlands, using panel data analysis. The study found that the growth of Indonesia's cocoa bean exports was significantly impacted by four variables, namely the export volume of cocoa beans, Indonesia's GDP, economic distance, and the population of export destination countries. On the other hand, the variables such as GDP of export destination countries, production, productivity, exchange rates, prices of world cocoa beans, harvested area, and domestic cocoa bean prices did not demonstrate any noteworthy impact on the exports. The development of sustainable cocoa bean exports holds great potential. If the Indonesian government wishes to improve cocoa bean production centers, a collaborative strategy is necessary, particularly among stakeholders to support the development of sustainable cocoa bean exports.